(untitled) (SCIENCE TIME JOURNAL, 2026)
The present study investigates the pedagogical and methodological significance of interactive games in teaching English as a foreign language. The research aims to analyze the impact of game-based learning on students’ motivation, communicative competence, vocabulary acquisition, and classroom interaction. The study employs qualitative analysis, comparative review of pedagogical literature, and observation of classroom practices. The findings indicate that interactive games function not merely as motivational tools but also as effective instruments for developing communicative skills and fostering learner-centered environments. The study contributes to the methodological framework of communicative language teaching by systematizing the functions and pedagogical benefits of interactive learning activities.